Application of chokeberry biochar as a modified additive to the vegetable lubricants: the tribological and rheological properties - Rafal Kozdrach; Pawel Radulski (Scientific Reports)
Abstract Effect of modifying a vegetable grease with different amounts of chokeberry biocarbon on its tribological and rheological properties. The aim of the research was to investigate the effect of the incorporation of biochar derived from the pyrolysis of chokeberry biomass at 500 and 700 °C respectively, in lubricants formulated with vegetable oil, on their functional characteristics in terms of tribology and rheology. Fumed silicon dioxide was utilized as a thickening agent, ensuring the production of lubricants with a consistency class of II. The biochar was introduced into the lubricating formulations in concentrations of 1, 3, and 5%. A rapeseed-based grease with commercial activated carbon served as the reference sample. The research focused on assessing how this innovative additive influenced both the tribological and rheological behaviors of the resulting lubricants. The study evaluated the effects of chokeberry-derived biochar on the wear resistance and scuffing prevention properties of the vegetable-based greases. Additionally, the biochar’s influence on various rheological parameters such as flow curves, viscosity profiles, hysteresis loops, and viscoelastic characteristics was analyzed. Results demonstrated that the biochar additive considerably enhanced the tribological and rheological performance of the tested rapeseed-based grease.